Can massive open online courses fill African evaluation capacity gaps? - Caitlin, Blaser Mapitsa; Linda, Khumalo; Hermine, Engel; Dominique, Wooldridge (African Evaluation Journal, 2019)
Theory of Change for Development is a free online course developed at an African institution to strengthen evaluation capacity in the region. Massive Open Online Courses (MOOCs) provide a platform for building skills at scale in the region. Scholars of evaluation have long pointed to a gap between supply and demand that frustrates both evaluation practitioners and commissioners. This article explores the possibilities and limitations of MOOCs to bridge this gap.
Keywords: Can massive open online courses fill African evaluation capacity gaps?